AKTIVITAS ANTIDIABETES EKSTRAK DAUN BELIMBING WULUH (Averrhoa bilimbi L) - Evi Sovia (JURNAL FARMASI GALENIKA, 2015)
Averrhoa bilimbi L have been known to have antidiabetic effect. The part of Averrhoa bilimbi L plant that usually used is leaf and fruit. While, the polar solvent often used to extracted the plant. The aim of this study is to investigated antidiabetic activity of Averrhoa bilimbi leaves extract with three various solvent. Averrhoa bilimbi leaves were extracted using three different solvent that are hexane, ethyl acetate and ethanol. Characterization dan phytochemistry screening of all extracts were done to get standarized extract. Antidiabetic activity was evaluated using alloxan induced diabetes rats. Fourthy wistar rats devided into ten groups that are normal group, control group that induced by alloxan and given CMC, and eight treatment group that induced by alloxan and given ethyl acetate and ethanol extract of Averrhoa bilimbi with 125, 250, and 500 mg/kg bw doses, 500 mg/kg bw of hexane extract and 0.65 mg/kg bw of glibenclamid. Blood glucose levels were measured before and after alloxan induction, and two weeks after treatment. The results showed that blood glucose level in control group (333.3±28.4g/dl) have significant difference (p<0.05) compared to treatment group that given Averrhoa bilimbi ethanol and ethyl acetate extract with 125,250 and 500mg/kb bw doses, that are 101±59.6; 94.8±8.9; 77.8±15.2; 125±25.3; 158±44.9 and 119±39.9 respectively. Meanwhile, ethanol is the best solvent to extract Averrhoa bilimbi and the most effective dose is 125 mg/kg bw. Ethanol extract also have better antidiabetic activity than that of ethyl acetate extract, whereas hexane extract have not antidiabetic activity.